Investigation of the Flow Characteristics of Methane Hydrate Slurries with Low Flow Rates - Cuiping Tang; Xiangyong Zhao; Dongliang Li; Yong He; Xiaodong Shen; Deqing Liang (Energies, 2017)
Gas hydrate blockage in pipelines during offshore production becomes a major problem with increasing water depth. In this work, a series of experiments on gas hydrate formation in a flow loop was performed with low flow rates of 0.33, 0.66, and 0.88 m/s; the effects of the initial subcooling, flow rate, pressure, and morphology were investigated for methane hydrate formation in the flow loop. The results indicate that the differential pressure drop (ΔP) across two ends of the horizontal straight pipe increases with increasing hydrate concentration at the early stage of gas hydrate formation. When the flow rates of hydrate fluid are low, the higher the subcooling is, the faster the transition of the hydrates macrostructures. Gas hydrates can agglomerate, and sludge hydrates appear at subcoolings of 6.5 and 8.5 °C. The difference between the ΔP values at different flow rates is small, and there is no obvious influence of the flow rates on ΔP. Three hydrate macrostructures were observed: slurry-like, sludge-like, and their transition. When the initial pressure is 8.0 MPa, large methane hydrate blockages appear at the gas hydrate concentration of approximately 7%. Based on the gas–liquid two-phase flow model, a correlation between the gas hydrate concentration and the value of ΔP is also presented. These results can enrich the kinetic data of gas hydrate formation and agglomeration and provide guidance for oil and gas transportation in pipelines.